Hubungan Kelentukan, Kekuatan Lengan dan Daya Ledak Tungkai Dengan Renang Gaya Dada pada Mahasiswa FIK UNM Makassar. - M. Rachmat Kasmad; Mutmainnah Basit (UNIVERSITAS NEGERI MAKASSSAR, 2021)
This study aims to: (1) To determine whether there is flexibility in the ability Relations swimming breaststroke of students at FIK UNM Makassar. (2) To determine whether there is a relationship of arm strength with the ability of swimming breaststroke of students at FIK UNM Makassar. (3) To determine whether there is a connection with the explosive power of the legs breaststroke swimming ability in students of FIK UNM Makassar. (4) To determine whether there is a connection joint flexibility, muscle strength and explosive power leg sleeve with the ability of swimming breaststroke of students at FIK UNM Makassar. This type of research is descriptive correlational. population in this study were all students of the first half and a third son who totaled 300 people. with a sample of 40 students, the technique used is simple random sampling. Data analysis technique used is regression. Based on these results it can be concluded that: (1) there is a connection flexibility on the ability of swimming breaststroke of students at FIK UNM Makassar values obtained regression coefficient of determination -0.158 with a significant level of 0.000 <α0,05, for determination coefficient of 0.303. This means that 30.3% flexibility relationship to the ability of swimming breaststroke of students at FIK UNM Makassar. (2) there is a connection arm muscle strength in the ability of swimming breaststroke of students at FIK UNM Makassar values obtained regression coefficient of determination -0.307 with a significant level of 0.000 <α0,05, for determination coefficient of 0.739. This means that 73.9% of muscle strength relations arm of the ability of swimming breaststroke at Fik UNM Student Makassar. (3) there is a connection limb explosive power of the ability of swimming breaststroke of students at FIK UNM Makassar values obtained regression coefficient of determination -0.129 with a significant level of 0.000 <α0,05, for determination coefficient of 0.490. This means 49% correlation explosive power of the legs of the ability of swimming breaststroke in Student Fik UNM Makassar (4) There is a connection of flexibility, muscle strength of arms, explosive leg with the ability of swimming breaststroke of students at FIK UNM Makassar obtained regression value (Ro) 0.906 with the level of significance in the column sig, the amount of (0.000) <α 0.05 for the value of R Square (coefficient) 0821. This means that 82.1% relations flexibility, arm muscle strength, explosive power leg together on the ability of swimming breaststroke of students at FIK UNM Makassar